Writing on the Body? Thinking Through Gendered Embodiment and Marked Flesh : Thinking Through Gendered Embodiment and Marked Flesh. - Inckle, Kay (Cambridge Scholars Pub., 2007)
This groundbreaking piece of work establishes a "position of embodiment" as an ethically salient epistemological and empirical strategy for understanding, representing, and experiencing gendered embodiment and marked flesh. Developing an embodied, feminist critique of the sociology of the body, the author integrates this position with some of the most recent developments in qualitative methodologies and creative research practices in order to engage with, and represent, women's experiences of ...